Mechanistic Evidence of Andrographis paniculata (Burm. f.) Wall. ex Nees, Pelargonium sidoides DC., Echinacea Species and a Combination of Hedera helix L., Primula veris L./Primula elatior L. and Thymus vulgaris L./Thymus zygis L. in the Treatment of Acute, Uncomplicated Respiratory Tract Infections: A Systematic Literature Review and Expert Interviews - Liesbeth B. M. Veldman; Eefje Belt-Van Zoen; Erik W. Baars (MDPI AG, 2023)
Reducing inappropriate antibiotic (AB) use by using effective non-antibiotic treatments is one strategy to prevent and reduce antimicrobial resistance (AMR). Andrographis paniculata (Burm. f.) Wall. ex Nees, Pelargonium sidoides DC., Echinacea species and a combination of ivy (Hedera helix L.), primrose (Primula veris L./Primula elatior L.) and thyme (Thymus vulgaris L./Thymus zygis L.) have promising clinical effects in uncomplicated, acute upper respiratory tract infections (URTI) treatment. However, mechanistic evidence of these herbal treatments is lacking. The objective of this Pstudy is to provide an overview of mechanistic evidence for these effects. Thirty-eight databases were searched. Included studies were mechanistic studies (in vitro, animal, and human studies and reviews) on these herbs; published before June 2021. Non-mechanistic studies or studies on combinations of herbs other than ivy/primrose/thyme were excluded. Furthermore, three experts in traditional, complementary and integrative healthcare (TCIH) research and pharmacognosy were interviewed to collect additional expert knowledge. The results show that A. paniculata acts through immunomodulation and antiviral activity, possibly supplemented by antibacterial and antipyretic effects. P. sidoides acts through antiviral, indirect antibacterial, immunomodulatory and expectorant effects. Echinacea species likely act through immunomodulation. The combination of ivy/primrose/thyme combines secretolytic and spasmolytic effects from ivy with antibacterial effects from thyme. Studies on primrose were lacking. This mechanistic evidence supports the difference-making evidence from clinical studies, contributes to evidence-based recommendations for their use in URTI treatment, and guides future mechanistic studies on URTI treatments.